Quality management in property maintenance management focus on industrial building / Shuriati Samsu - Samsu, Shuriati (2001)
In every country, especially in Malaysia, the most valuable capital asset is: its building stock. The important about building and property maintenance has long been a debatable matter whether in the private or public sector. Therefore, with the rapid increase >»of our building stock and imported technology in building construction, there has been a growing concern over the maintenance and management of such properties. Many organizations at various types of business have demand a high standard of maintenance management in property without consciously providing sufficient concentration on quality management in property maintenance management. Only in recent times, they will come to realize the crucial importance of quality management of property maintenance management in order to preserve the business they run. Many have realized that the condition of their assets and business properties do really affect the condition of work atmosphere, customers' opinion and preferences, and eventually the income flow of the business. However, there is also concern amongst the professionals, over the fact that with their knowledge and skills, they have been under utilized due to the lack of concern over building maintenance. The management of building maintenance requires great care in selecting skilled personnel and this normally involves basic principles in forming maintenance management organization.